The Effect of Using IPod Technology on EFL College Students’ Writing Skill - Al-Subaihat, Thekrayat Ali; Bataineh, Ahmad Mousa (Journal of Educational and Psychological Sciences, 2020)
This study aimed to explore the effect of using IPod technology on EFL students’ writing skill. It also aimed to investigate whether teaching writing via using IPod Technology is better than the conventional method of teaching. To carry out the study, 65 male and female undergraduate EFL students who registered for a Writing 2 course at, Al-alBayt University, in the second semester of the academic year 2015/2016 were chosen as participants of the study. They were assigned randomly into two groups: Group one consisted of 35 students, which was chosen as an experimental group and was taught writing using IPod technology and group two consisted of 30 students, which was assigned as a control group and was taught using conventional method of teaching. Both groups were taught the same material, on the same days of the week, and on the same period. Both groups sat for a pre-post-test to assure that both groups have the same linguistic ability level in the aspects of writing. The Statistical Package for Social Sciences (SPSS) software was used to conduct the required statistical analysis of the data related to the objectives of the study. Means, standard deviations, one-way ANOVA, and Scheffe tests were used for all the variables of the study. Data were collected within eight weeks. The findings of the study showed that there were statistically significant differences between the mean scores of the experimental group and control group students’ writing performance in favor of the experimental group. Thus progress might be due to using IPod technology. A number of related recommendations were presented to the Ministry of Education and the teachers.